Risk Factors and Nomogram for Common Bile Duct Stricture in Chronic Pancreatitis: A Cohort of 2153 Patients. Issue 3 (March 2019) - Hao, Lu; Bi, Ya-Wei; Zhang, Di; Zeng, Xiang-Peng; Xin, Lei; Pan, Jun; Wang, Dan; Ji, Jun-Tao; Du, Ting-Ting; Lin, Jin-Huan; Ye, Bo; Zou, Wen-Bin; et al.
Abstract : Goals: To identify the risk factors and develop nomograms for common bile duct (CBD) stricture in chronic pancreatitis (CP) patients. Background: CBD stricture is a common complication in CP and has a variable clinical presentation ranging from asymptomatic to overt jaundice and cholangitis. Study: Patients with CP admitted to Changhai Hospital (Shanghai, China) from January 2000 to December 2013 were enrolled. Cumulative rates of CBD stricture after onset and diagnosis of CP were calculated. Patients were randomly assigned, in a 2:1 ratio, to the training and validation cohort. On the basis of the training cohort, risk factors for CBD stricture and symptomatic CBD stricture were identified through Cox proportional hazards regression model, and nomograms was developed, respectively. Internal and external validations were performed based on the training and validation cohort, respectively. Results: With a total of 2153 patients, the median duration of follow-up was 7.0 years. CBD strictures were detected in 340 (15.8%) patients, whereas 159 of them were symptomatic. Male gender, age at onset of CP, smoking, body mass index, and morphology of main pancreatic duct were identified risk factors for CBD stricture development. Age at onset of CP, body mass index, and type of pain were identified risk factors for symptomatic CBD stricture development. Both nomograms achieved good concordance indexes with well-fitted calibration curves. Conclusions: The nomogram achieved an individualized prediction of symptomatic CBD stricture development in CP patients. It may help the early diagnosis and intervention of symptomatic CBD stricture and reduce the rates of severe adverse events. Abstract : Supplemental Digital Content is available in the text.